(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
Bajaj, M. (Ed.) (2008). Encyclopedia of Peace Education. Charlotte, North Carolina: Information Age Publishing, Inc. ISBN: 978-1-59311-898-3.